2003
DOI: 10.1515/bc.2003.050
|View full text |Cite
|
Sign up to set email alerts
|

Invasiveness of Transformed Human Breast Epithelial Cell Lines Is Related to Cathepsin B and Inhibited by Cysteine Proteinase Inhibitors

Abstract: The activities'of the lysosomal cysteine proteinases cathepsin B and L are regulated by their endogenous inhibitors, stefins A and B, and cystatin C, and their imbalance may be associated with increased invasiveness and development of the malignant cell phenotype. The aim of this study was to investigate mRNA, protein and activity levels of the above proteins in relation to in vitro invasiveness and to the reported in vivo tumorigenicity of four human breast tumor cell lines: the spontaneously immortalized cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…The antiangiogenic effects of pCU are also in agreement with previous studies showing that inhibition of uPAR activity suppressed retinal neovascularization, possibly through a reduction in cell-associated proteolytic activity, cell signaling or cell-matrix adhesion necessary for cell migration during angiogenesis (McGuire et al, 2003). Synthetic cysteine proteinase inhibitors, selective for cathepsin B, have been shown to significantly reduce the invasiveness of MCF10AT cells (Bervar et al, 2003). Several studies using selective inhibitors of uPA or small, synthetic cyclic, competitive uPA antagonists derived from the binding sites of uPAR resulted in highly significant reduction of tumor burden (Evans et al, 1998;Sato et al, 2002).…”
Section: Cathepsin B and Upar Sirna Suppresses Intracranial Tumor Growthsupporting
confidence: 89%
See 1 more Smart Citation
“…The antiangiogenic effects of pCU are also in agreement with previous studies showing that inhibition of uPAR activity suppressed retinal neovascularization, possibly through a reduction in cell-associated proteolytic activity, cell signaling or cell-matrix adhesion necessary for cell migration during angiogenesis (McGuire et al, 2003). Synthetic cysteine proteinase inhibitors, selective for cathepsin B, have been shown to significantly reduce the invasiveness of MCF10AT cells (Bervar et al, 2003). Several studies using selective inhibitors of uPA or small, synthetic cyclic, competitive uPA antagonists derived from the binding sites of uPAR resulted in highly significant reduction of tumor burden (Evans et al, 1998;Sato et al, 2002).…”
Section: Cathepsin B and Upar Sirna Suppresses Intracranial Tumor Growthsupporting
confidence: 89%
“…Cathepsin B was shown to activate precursors of serine proteinases to their active forms, such as pro-uPA (Kobayashi et al, 1991) and metalloproteinases, such as pro-stromelysin (Murphy et al, 1992). Invasiveness through Matrigel of transformed human breast epithelial cell lines was related to cathepsin B expression and was inhibited by cysteine proteinase inhibitors (Bervar et al, 2003). In ovarian cancer cells, inhibition of cell surface cathepsin B prevents activation of pro-uPA, and subsequently, invasion of the carcinoma cells through Matrigel (Kobayashi et al, 1993).…”
Section: Cathepsin B and Upar Sirna Suppresses Intracranial Tumor Growthmentioning
confidence: 99%
“…Intracellular and extracellular cathepsin B activity contributes to the in vitro invasiveness of MCF10AT cells (Premzl et al, 2003). Synthetic cysteine proteinase inhibitors, selective for cathepsin B, have been shown to significantly reduce the invasiveness of MCF10AT cells (Bervar et al, 2003). Increased cathepsin B activity was observed in the invasive tumor regions of human colon cancer samples (Emmert-Buck et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the expression and/or activity of cathepsins and their inhibitors may be used as indicators for evaluating survival rates and recurrence risks (10,(20)(21)(22)(23)(24). Recent studies have shown that small molecule inhibitors of recombinant proteases (stefin A/B, AC-LVK-CHO) and a specific cathepsin B inhibitor (CA-074) can suppress the metastasis of ovarian and breast cancers (25)(26)(27). In malignancies including glioma, meningioma, prostate cancer and oral cancer, RNA interference was used to down-regulate tumor-related genes including cathepsin B, and the results showed significantly inhibited invasion and metastasis (13,14,21,28).…”
mentioning
confidence: 99%